A new American species of the spider genus Pimoa (Araneae, Pimoidae) - Hormiga, Gustavo; Lew, Stephen (Zootaxa, 2014)
The family Pimoidae is a small lineage of araneoid spiders distributed in Western North America, Southern Europe and Asia. Currently four genera and 37 extant species have been described (Platnick 2014). Pimoidae are represented in North America by 14 species classified in the genera, Pimoa Chamberlin & Ivie, 1943, and Nanoa Hormiga, Buckle & Scharff, 2005. The latter genus is monotypic and was recently described based on very few specimens collected in California and Oregon. With the exception of Nanoa enana Hormiga, Buckle & Scharff, 2005, no other pimoid has been described from North America since publication of the family monograph of Hormiga (1994). Since the revision of Pimoa in the family monograph, five new species of Pimoa have been described from China (Griswold et al. 1999, Xu & Li 2007) and one from India (Trotta 2009). In addition, other Asian pimoid species have been recently described in the genera Weintrauboa Hormiga, 2003 and Putaoa Hormiga & Tu, 2008 (Hormiga 2003, Hormiga 2008, Hormiga & Tu 2008, Xu & Li 2009, Yang et al. 2006). In this paper we describe a new species of the genus Pimoa from California.